COST EFFECTIVENESS OF TOPICAL GLYCERYL TRINITRATE VERSUS LATERAL INTERNAL SPHINCTEROTOMY FOR CHRONIC ANAL FISSURE - Samad, Abdul; Khanzada, Tariq Wahab; Sushel, Champa (Journal of Postgraduate Medical Institute, 2011)
Objective: To compare the cost effectiveness of initial use of topical glyceryl trinitrate (GTN) before lateral internal sphincterotomy against the sphincterotomy as primary treatment modality for chronic anal fissure. Material and Methods: This prospective randomized study was conducted at Isra University Hospital, Hyderabad between November 2004 and October 2005. Fifty patients fulfilling the criteria were randomised into two equal groups. One group was treated with topical GTN ointment and other group with lateral internal sphincterotomy. Patients were followed up for one year. In case of failure of treatment or recurrence in GTN group, the patients were subjected to lateral sphincterotomy. The total expenditures of treatment in both groups were separately calculated and compared. Results: Pain relief was observed in 92% of the patients in both the groups after 6 weeks. Complete healing of fissure was observed in 92% and 88% of the patients in GTN group and sphincterotomy group respectively after 6 weeks. Recurrence was observed in 16% of the patients in GTN group and none in sphincterotomy group after one year. The sphincterotomy was avoided in 76% of the patients in GTN group during one year. The total expenditure of GTN group was Pakistani Rupees (PKR) 139500 and of sphincterotomy group was PKR 387500; about 2.8 time the expenditure of GTN group. Conclusion: The initial use of topical GTN before sphincterotomy against the sphincterotomy as primary treatment modality for chronic anal fissure is cost effective and provides substantial monetary benefit.